2017
DOI: 10.1016/j.bpj.2016.11.2823
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of Reversible Phase Separation in Living, Unperturbed Cell Membranes

Abstract: Hallmarks of Reversible Phase Separation in Living, Unperturbed Cell Membranes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 113 publications
(165 reference statements)
0
3
0
Order By: Relevance
“…Despite this simple definition and much supporting evidence [10][11][12][13][14][15][16][17] , there remains significant controversy about the existence and functionality of raft domains in living cells 3 . In large part, the controversies persist because raft domains have not been directly, microscopically observed in living cell PMs, although liquid lipid-driven domains have been imaged directly in yeast vacuoles 17,18 . PM nanodomains may be difficult to image due to the limits on spatial and temporal resolution of currently available technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this simple definition and much supporting evidence [10][11][12][13][14][15][16][17] , there remains significant controversy about the existence and functionality of raft domains in living cells 3 . In large part, the controversies persist because raft domains have not been directly, microscopically observed in living cell PMs, although liquid lipid-driven domains have been imaged directly in yeast vacuoles 17,18 . PM nanodomains may be difficult to image due to the limits on spatial and temporal resolution of currently available technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of lateral phase separation in the plane of the lipid monolayers and bilayers in terms of mobility of membrane-anchored motifs and lipid conformations have come a long way since the early original work carried out 30–50years ago. Several recent experimental and computational studies have shown stark evidence of lateral phase separation in vitro model ternary and quaternary lipid mixtures and in vivo cell membranes. The model ternary in vitro systems generally consist of a saturated lipid, unsaturated lipid, and cholesterol. Depending on the cholesterol content, ternary systems show two-phase coexistence as “liquid-ordered” L o and “liquid-disordered” L d phases at higher cholesterol concentrations and “liquid-ordered gel” L β and “liquid-disordered” L d phases at lower cholesterol concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The study of lateral phase separation in the plane of the lipid monolayers and bilayer in terms of mobility of membrane anchored motifs and lipid conformations have come a long way since the early original work carried out 30-50 years ago [1][2][3][4][5][6][7][8][9][10]. Several recent experimental and computational studies have shown stark evidence of lateral phase separation in in-vitro model ternary [11][12][13][14][15] and quaternary lipid mixtures [16][17][18] and in in-vivo cell membranes [19][20][21][22][23]. The model ternary in-vitro systems generally consists of a saturated lipid, unsaturated lipid and cholesterol.…”
Section: Introductionmentioning
confidence: 99%